Non-covalent interactions in MOFs: a quantum approach to gas adsorption and molecular encapsulation - Medel, Erika; Vargas, Rubicelia (Frontiers in Chemistry, 2025)
Non-covalent interactions are fundamental for understanding the chemical behavior of porous materials with guest molecules, which is key for designing new materials. The Quantum Theory of Atoms in Molecules has enabled us to visualize and analyze non-covalent interactions in host-guest systems, particularly with Metal-Organic Frameworks (MOFs) as hosts. Using this tool, we have investigated the adsorption mechanisms of highly polluting gases such as CO and CO2 in InOF-1, MFM-300(Sc), and MFM-300(In). We have also explained the preferential adsorption of molecules in NOTT-401 and related changes in gas capture due to the functionalization of MOF pores. Furthermore, our group has extensively studied functionalization in the encapsulation and release of pharmacologically relevant molecules in BioMOFs, which are biocompatible, bioinspired MOFs. In this paper, we revisit our previous work while presenting new results from a systematic study of molecules from the phenylethylamine family as guests in BioMOFs, demonstrating the potential of our methodology to study new materials, such as Hydrogen-Bonded Organic Frameworks or Covalent Organic Framework.